PENDAMPINGAN PENGISIAN SPT TAHUNAN ORANG PRIBADI DI WILAYAH SIDOARJO SELATAN - Wicaksono, Achmad; Fahriani, Dian; Muzakki, Kafidin; Novie, Muhafidhah (Fakultas Teknik, Universitas Bangka Belitung, 2023)
This community service activity is carried out with the aim of helping the people of the South Sidoarjo region in fulfilling their tax obligations, namely reporting individual annual SPTs. The service team’s method is providing assistance and services directly to the community present at the post formed by KPP Pratama South Sidoarjo. Before providing assistance, the service team first carried out a recruitment process for tax volunteers who came from accounting study program students at Nahdlatul Ulama University, Sidoarjo. The results of the service showed that all the people present at the post could be served well by the Tax Volunteers on duty so that the obligation to report SPT could be carried out correctly and on time. Apart from that, it was seen that the majority of people present were satisfied with the performance shown by the tax volunteers on duty.